10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Non-Māori with mental health and substance use conditions experience relative privilege evident in health outcomes when compared to Māori (the Indigenous population) in New Zealand. This paper will explore physical healthcare experiences for Māori with a mental health and/or substance use condition. This qualitative study was one component of the Tupuānuku Project investigating the enablers and barriers that effect access to quality physical healthcare for people with mental health and substance use conditions. An intersectional, critical theory approach was used to examine how power and structural inequities informed the context and findings of this study, as well as influencing the study design, research process, and positioning of the research team. Tikanga Māori (cultural protocols) facilitated cultural safety. Nine semi-structured interviews were completed with Māori participants with mental health and substance use conditions, to further explore their experiences of physical healthcare. Thematic analysis was used. Two themes were derived essential to inclusive health ecosystems: (1) enhancing structural accessibility and (2) nurturing interpersonal relationships. Embedded within the two themes were recommendations required to cultivate a more inclusive, equitable health ecosystem in which to nourish the physical health of Māori with mental health and substance use conditions. Findings were consistent with other New Zealand research in highlighting the need for whole health system transformation to address the structural factors that produce health inequities for Māori with mental health and substance use conditions.